16=p-(-3)

Simple and best practice solution for 16=p-(-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16=p-(-3) equation:


Simplifying
16 = p + -1(-3)

Multiply -1 * -3
16 = p + 3

Reorder the terms:
16 = 3 + p

Solving
16 = 3 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
16 + -1p = 3 + p + -1p

Combine like terms: p + -1p = 0
16 + -1p = 3 + 0
16 + -1p = 3

Add '-16' to each side of the equation.
16 + -16 + -1p = 3 + -16

Combine like terms: 16 + -16 = 0
0 + -1p = 3 + -16
-1p = 3 + -16

Combine like terms: 3 + -16 = -13
-1p = -13

Divide each side by '-1'.
p = 13

Simplifying
p = 13

See similar equations:

| 10m+8b-12=0 | | -15+7x=-79 | | (x+3)+(y-5)=36 | | -25(d+2)= | | 14x+9y=310 | | 16.4(2x+11)=6x+33 | | 2990=4*660+6y | | 12x+9y=310 | | -2(z-9)=-24 | | y-10=-2(x+2) | | 7u-6u+2=20 | | 2990=4*650+6y | | .5x-9=.2x | | Y-2=-1(x+7) | | 4(cos^2(2x))-2=0 | | -25d-50= | | 2990=4*640+6y | | x+y-8x+6y-125=0 | | X-15=-50 | | 70=(4y-30) | | 3x-10y=-22 | | (1-x)+3x=-2(x+1) | | 5x-20+2x+53=180 | | -4z-1=12 | | x+5/x+4=7 | | (-8b)-(-12b)+2=(-10) | | 5x-20+2x-53=180 | | 7b-14= | | 14m-3=12m-15 | | 7t-5t-1=3 | | 2(w+2)=10 | | Y-3=8(x-2) |

Equations solver categories